Tolerogenic versus Inflammatory Activity of Peripheral Blood Monocytes and Dendritic Cells Subpopulations in Systemic Lupus Erythematosus - Carvalheiro, T (2012)
Abnormalities in monocytes and in peripheral blood dendritic cells (DC) subsets have been reported in systemic lupus erythematosus (SLE). We aim to clarify the tolerogenic or inflammatory role of these cells based on ICOSL or IFN-α and chemokine mRNA expression, respectively, after cell purification. The study included 18 SLE patients with active disease (ASLE), 25 with inactive disease (ISLE), and 30 healthy controls (HG). In purified plasmacytoid DC (pDC) was observed a lower ICOSL mRNA expression in ASLE and an increase in ISLE; similarly, a lower ICOSL mRNA expression in monocytes of ALSE patients was found. However, a higher ICOSL mRNA expression was observed in ASLE compared to HG in myeloid DCs. Interestingly, clinical parameters seem to be related with ICOSL mRNA expression. Regarding the inflammatory activity it was observed in purified monocytes and CD14(-/low) CD16(+) DCs an increase of CCL2, CXCL9, and CXCL10 mRNA expression in ASLE compared to HG. In myeloid DC no differences were observed regarding chemokines, and IFN-α mRNA expression. In pDC, a higher IFN-α mRNA expression was observed in ASLE. Deviations in ICOSL, chemokine, and IFN-α mRNA expression in peripheral blood monocytes and dendritic cells subpopulations in SLE appear to be related to disease activity.